Effectiveness of the Invisalign Mandibular Advancement Appliance in Children with Class II Division 1 Malocclusion - So-Youn An; Hyeon-Jin Kim; Ho-Uk Lee; Sang-Ho Bak; Hyo-Jin Kang; Youn-Soo Shim (The Korean Society of Dental Hygiene Science, 2023)
Background: This study aimed to determine the skeletal and dental effects in pediatric and adolescent Korean patients with Class II Division 1 malocclusion treated using the Invisalign Mandibular Advancement (MAⓇ) appliance. Methods: The study included patients aged 6 to 18 years who received orthodontic treatment with the MAⓇ appliance for Class II Division 1 malocclusion at the Department of Pediatric Dentistry, Wonkwnag University Daejeon Dental Hospital, between July 1, 2018, and December 31, 2021. The treatment group consisted of 20 patients, 10 boys and 10 girls. The control participants were also 10 boys and 10 girls. Lateral cephalometric radiographs were taken before and after treatment, and 41 measurements of skeletal and dental changes were measured and analyzed using the V-CephTM 8.0 (Osstem Implant). All analyses were performed using SPSS software (IBM SPSS for Windows, ver 26.0; IBM Corp.), and statistical significance was tested using paired and independent samples t-tests for within-group and between-group comparisons, respectively. Results: The patients in the treatment group showed significant decreases in ANB (A point, Nasion, B point), maxillary protrusion, maxillary anterior incisor labial inclination, and maxillary protrusion after treatment. However, when compared with the growth changes observed in the control group, only ANB and maxillary protrusion decreased, with no significant differences in SNA, SNB, and mandibular length. Conclusion: Collectively, the results of this study confirm that the use of MAⓇ appliance in pediatric and adolescent Korean patients with Class II Division 1 malocclusion results in a reduction of anteroposterior skeletal and dental disharmony.